Eritrea - Cultural Assets Rehabilitation Project - Mastri, Lawrence (World Bank, Washington, DC, 2012)
The Cultural Assets Rehabilitation Project aimed to strengthen the management of public records in order to contribute to the development of a historiography of Eritrea while improving the efficiency of the public sector. The project will also strengthen the management of public records both to contribute to the development of a historiography of Eritrea while improving the efficiency of the public sector. Overall the project was able to meet its objectives of testing out and developing the means for more fully integrating the conservation and management of cultural assets into local and national economic development. Furthermore, it promoted learning in many areas that are central to development at an institutional and skills level.